KORELASI ANTARA USIA KRONOLOGIS AWAL MASUK SEKOLAH TERHADAP PRESTASI BELAJAR - Mar'atun Aslamiah R (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract: This research was conducted based on the problem found in the field indicating that many children were enrolled to school under the age specified by the government (seven years old). It was assumed that the children who went to Elementary School earlier found some obstacles in learning. This was quite different from those entering school by the age of 7. To deal with this problem, the researcher was interested to reveal whether there was any correlation between chronological age when entering school and the children learning achievement at SDN 09 Koto Luar, Padang. This was a correlational research which was intended to see whether one variable had a correlation with the other one. The data was gotten through documentation method to see the chronological age of the children when entering school and the children scores from the first semester in the first grade to the first semester in the sixth grade. The data was analyzed by using the Correlation Product Moment requiring that the hypothesis accepted when the value of rcalculated was bigger than rtable on the significance level 5%. The result of data analysis showed that the value of rcalculated was 0,08 and rtable was 0,29. This result indicated that the hypothesis was accepted. Hence, it was concluded that there was no significant correlation between chronological age of the children when entering school and their learning achievement at SDN 09 Koto Luar,Padang. It was recommended to the upcoming researcher to study other factor which were beyond the researcher’s concern. Kata Kunci : Korelasi; Usia Kronologis Awal Masuk Sekolah; Prestasi Belajar